Ultrafine particle size as a tracer for aircraft turbine emissions. (August 2016) - Riley, Erin A.; Gould, Timothy; Hartin, Kris; Fruin, Scott A.; Simpson, Christopher D.; Yost, Michael G.; Larson, Timothy
Abstract: Ultrafine particle number (UFPN) and size distributions, black carbon, and nitrogen dioxide concentrations were measured downwind of two of the busiest airports in the world, Los Angeles International Airport (LAX) and Hartsfield-Jackson International Airport (ATL – Atlanta, GA) using a mobile monitoring platform. Transects were located between 5 km and 10 km from the ATL and LAX airports. In addition, measurements were taken at 43 additional urban neighborhood locations in each city and on freeways. We found a 3–5 fold increase in UFPN concentrations in transects under the landing approach path to both airports relative to surrounding urban areas with similar ground traffic characteristics. The latter UFPN concentrations measured were distinct in size distributional properties from both freeways and across urban neighborhoods, clearly indicating different sources. Elevated concentrations of Black Carbon (BC) and NO2 were also observed on airport transects, and the corresponding pattern of elevated BC was consistent with the observed excess UFPN concentrations relative to other urban locations. Graphical abstract: Highlights: Spatial measurements of ultrafine particle number (PN) and diameter in two cities. PN concentrations more than 5 km from airport are similar to those on freeways. Spatial distribution of mean ultrafine particle diameter is distinct near airport. Ratio of PN to black carbon is higher beneath approach path than elsewhere.